Efektivitas Pemanfaatan Artificial Intelligence (AI) dalam Layanan Bimbingan dan Konseling Pada Mahasiswa di Perguruan Tinggi: A Systematic Literature Review (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The development of digital technology has encouraged the use of Artificial Intelligence (AI) in guidance and counseling services in higher education as an alternative to address the limitations of conventional services. This study aims to examine the use of AI and its effectiveness in guidance and counseling services for students in higher education. The research method used was a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) steps. The literature search was conducted through Scopus, Google Scholar, and SpringerLink databases for articles published between 2021 and 2026. Based on the identification, screening, and selection process, 10 articles met the inclusion criteria for analysis. The results showed that AI is utilized in the form of counseling chatbots, academic and career recommendation systems, and student mental health support platforms. The use of AI has been shown to increase service efficiency, expand counseling access, encourage student self-disclosure, and support more personalized and responsive services. However, AI still has limitations in building empathy, therapeutic relationships, and in-depth emotional understanding. Furthermore, challenges such as data privacy, algorithmic bias, and digital literacy still require attention. Therefore, AI is more appropriately used as a supporting technology that complements, rather than replaces, the role of human counselors.